N-acetylglucosamine modification in the lumen of the endoplasmic reticulum - Ogawa, Mitsutaka; Sawaguchi, Shogo; Furukawa, Koichi; Okajima, Tetsuya (Biochimica et biophysica acta, 2015)
O-linked β-N-acetylglucosamine (O-GlcNAc) modification of epidermal growth factor (EGF) domains catalyzed by EGF domain O-GlcNAc transferase (EOGT) is the first example of GlcNAc modification in the lumen of the endoplasmic reticulum (ER). This review summarizes current knowledge on the EOGT-catalyzed O-GlcNAc modification of EGF domains obtained through biochemical characterization, genetic analysis in Drosophila, and identification of human EOGT mutation. Additionally, this review discusses GTDC2—another ER protein homologous to EOGT that catalyzes the GlcNAc modification of O-mannosylated α-dystroglycan—and other components of the biosynthetic pathway involved in GlcNAc modification in the ER lumen. GlcNAc modification in the ER lumen has been identified as a novel type of protein modification that regulates specific protein function. Moreover, abnormal GlcNAc modification in the ER lumen is responsible for Adams–Oliver syndrome and Walker–Warburg syndrome. Elucidation of the biological function of GlcNAc modification in the ER lumen will provide new insights into the unique roles of O-glycans, whose importance has been demonstrated in multifunctional glycoproteins such as Notch receptors and α-dystroglyan. •O-GlcNAc modification of EGF domains is the first example of GlcNAc modification in the ER lumen.•EOGT-catalyzed O-GlcNAc modification has been analyzed through biochemical characterization and genetic studies in Drosophila.•GTDC2, another ER protein homologous to EOGT, catalyzes GlcNAc modification of O-mannosylated α-dystroglycan.•Abnormal GlcNAc modification in the ER lumen is responsible for Adams–Oliver syndrome and Walker–Warburg syndrome.•GlcNAc modification in the ER lumen is a novel type of protein modification that regulates specific protein function.